A Case Report on Idiopathic Polyneuritis Cranialis Multiplex: A Rare Presentation of Guillian Barre Syndrome - George, Anna; S Shahul, Khadheeja; R, Subhala; J, Tijisha Mol (Indian Journal of Pharmacy Practice)
Polyneuritis Cranialis (PNC), a very infrequent disorder of multiple cranial nerve palsies without peripheral nerve involvement, is a variant of Guillain-Barré Syndrome (GBS). Facial weakness often combined with ocular signs such as ophthalmoplegia, ptosis, or papillary changes and bulbar signs like dysarthria or dysphagia, are shown by the majority of patients. It is a very uncommon disease that poses many challenges for early detection and management. Presented here is the case report of a 38-year-old male patient with recurrent headaches, a hallmark symptom of PNC, along with horizontal and vertical diplopia consistent with left 4th and 6th nerve paralysis.
Keywords: Polyneuritis cranialis; Guillian-Barre syndrome; Diplopia; Nerve palsies